DESAFIOS E RESULTADOS DO PROJETO DE PESQUISA EM MECATRÔNICA NA UNIJUÍ - Valdiero, Antonio C.; Andrighetto, Pedro L.; Gilapa, Genaro M. M.; Rafikov, Marat; Yansheng, Jiang; Bavaresco, Delair; Czyzesk, Charles V. S.; Carlotto, Leonardo; Gonçalves, Alexandre (Salão do Conhecimento, 2013)
Resumo